1996
DOI: 10.1007/bf01985721
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fertilizer placement on nitrogen uptake and yield of wheat and maize in Chinese loess soils

Abstract: Field trials were carried out to study the fate of 15N-labelled urea applied to summer maize and winter wheat in loess soils in Shaanxi Province, north-west China. In the maize experiment, nitrogen was applied at rates of 0 or 210 kg N ha-1, either as a surface application, mixed uniformly with the top 0.15 m of soil, or placed in holes 0.1 in deep adjacent to each plant and then covered with soil. In the wheat experiment, nitrogen was applied at rates of 0, 75 or t50 kg N ha -3, either to the surface, or inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 13 publications
3
41
0
5
Order By: Relevance
“…Locally recommended maize varieties were used, i.e., Yandan No.12 in 1993-1997, Shandannong No.1 in 1998, and Jindan No.34 in 1999-2004. The N and P fertilizers were urea (46% N) and superphosphate (7% P) in a ratio of N to P of 1:0.44.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Locally recommended maize varieties were used, i.e., Yandan No.12 in 1993-1997, Shandannong No.1 in 1998, and Jindan No.34 in 1999-2004. The N and P fertilizers were urea (46% N) and superphosphate (7% P) in a ratio of N to P of 1:0.44.…”
Section: Methodsmentioning
confidence: 99%
“…These practices commonly lead to soil drying and severe wind erosion in early spring. Erosion of fertile top soil, removal of crop residues (to feed animals and to be used as fuel for cooking with only partial return of manure and ashes to the cropped land) and burning of crop residues have led to nutrient depleted soils on various places (Rees et al 1997;Cai et al 2002;Peng et al 2006). Soil conservation and improved nutrient management practices are gaining interest of Chinese research and policy communities (Wang et al 1999(Wang et al , 2001(Wang et al , 2003Ju et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The use of trailing hose systems or surface banding for slurry application has been demonstrated to reduce NH 3 -N loss (Smith et al 2000) particularly when in conjunction with soil aeration (Bittman et al 2005). In the case of urea, application in bands at a minimum depth of 5 cm (Fenn and Miyamoto 1981) is recommended to improve N use efficiency (Rees et al 1996;Malhi et al 2001;Sommer et al 2004). Accordingly, ammonia emissions from urea incorporated in bands at 2.5 cm were 3% of applied N compared to 19% from broadcasted urea (Bouwmeester et al 1985).…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, Ling et al [6] found that the inorganic N concentration in the 6 -16 cm layers of paddy soil showed the following sequence: point deep fertilization > mixed fertilization with 3% soil > mixed fertilization with 10-cm top soil > broadcast. Rees et al [11] showed that the mineral nitrogen ( Cheng et al [15] found that with which the N fertilizers were mixed [6]. This is shown by the greater yields and NUEs after large particles of urea were applied compared with small particles of urea in rice field experiments [18].…”
Section: Discussionmentioning
confidence: 99%
“…An optimum fertilization model can reduce N loss, and increase crop yield and the NUE [11] [12] [13]. Rees et al [11] indicated that in the point-placement (hole-source fertilization) application were significant greater than in the corresponding surface-application and mixed-incorporation treatments. Wang et al [14] found that point deep placement can reduce the N fertilizer loss and improve the NUE.…”
Section: Introductionmentioning
confidence: 99%